Reactivity Initiated Transient Response of TRIGA with the Progress of Core Burnt - F. Haque; N.H. Badrun (Atom Indonesia, 2020)
This paper illustrates the effects on safety of TRIGA Mark-II research reactor of Bangladesh at its different steps of core burnt during reactivity induced transient. The modeling and simulation were carried by coupled point kinetics, neutronics, and thermal hydraulics code EUREKA-2/RR based on neutronics data calculated previously by Monte Carlo code for different burnt states of TRIGA core. Three burn steps until 150 MWD have been considered for present analysis which are regarded here as beginning of cycle (BOC); middle of cycle, MOC (75 MWD); and end of cycle, EOC (150 MWD). Initially, the results of steady state analysis obtained from EUREKA code for these three burn steps have been verified with that of COOLOD code. Based on consistency of the results from the two codes, transient simulation has been conducted considering reactor with non-function of scram. Reactivity inserted amount ranges within 0.001 to 0.02 dk/k with three durations of insertions of 0.1s, 1s, and 5s. Major parameters such as reactor core maximum power and fuel clad maximum temperature have been reported. The analysis presents transient pattern of these parameters due to change in amount and duration of inserted reactivity. The maximum imposed reactivity that causes the fuel clad to exceed its design temperature at each burn step has been evaluated in this study. It is also observed here for each amount and durations of inserted reactivity, maximum value of both power and clad temperature found to decrease with the progress of core burnt. These results obtained from this analysis will be useful for reactor operators and management team during core upgrading and modification program.